The feminist challenge to the Canadian Left, 1900-1918 - Newton, Janice, 1952- (McGill-Queen's University Press, 1995)
Newton argues that socialist women and their concerns posed a radical challenge to the male-dominated left. Early socialist women fought to be treated as equals and actively debated popular women's issues, including domestic work, women in industry, sexuality, and women's suffrage. They provided a unique and vibrant perspective on these issues and challenged the middle-class bias inherent in the women's movement. Broadening our understanding of Canadian social history, Newton analyses the intersection of two important social movements - the labour/socialist and the turn-of-the-century feminist movements - and draws conclusions that are essential for understanding the class and gender characteristics of social criticism and activism in this period.